アラタニ メイメイ サレタ ナンキョク チメイ - 国立極地研究所; コクリツキョクチケンキュウショ; NATIONAL INSTITUTE OF POLAR RESEARCH (国立極地研究所, 1976)
P(論文) The Antarctic Place-Names Committee of Japan worked out 9 new place names, which were officially approved by the Japanese Antarctic Research Expedition Headquaters, under date of 22nd November 1975. departmental bulletin paper